1969
DOI: 10.1620/tjem.98.107
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of Motor Endplate in Red, White and Intermediate Fibers of Mammalian Fast Muscle

Abstract: The fine structural differences of motor endplate among the red, white and intermediate muscle fibers of the rat fast limb muscle, M. extensor digitorum longus, were observed by the electron microscope.The motor endplate of the red fiber was small. The junctional folds were poorly developed and their number was small. In the white fiber, the motor endplate was large and the junctional folds were well developed and their number was far more numerous than those in the red fiber. In the intermediate fiber, the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

1969
1969
1995
1995

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…The qualitative ultrastructural features of the three fiber types have been utilized to classify fibers in investigations of the NMJ of myofiber types (Ogata, 1964;Ogata et al, 1967;Ogata and Murata, 1969a;Murata and Ogata, 1969;Padykula and Gauthier, 1970;Duchen, 1971). Stereological studies of the NMJ of fiber types and quantitative comparison of their morphology are nonexistent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qualitative ultrastructural features of the three fiber types have been utilized to classify fibers in investigations of the NMJ of myofiber types (Ogata, 1964;Ogata et al, 1967;Ogata and Murata, 1969a;Murata and Ogata, 1969;Padykula and Gauthier, 1970;Duchen, 1971). Stereological studies of the NMJ of fiber types and quantitative comparison of their morphology are nonexistent.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the ultrastructure of the neuromuscular junction (NMJ) described differences in this structure among the three mammalian fiber types (Ogata, 1964;Ogata et al, 1967;Ogata and Murata, 1969a;Murata and Ogata, 1969;Padykula and Gauthier, 1970;Duchen, 1971). The NMJ of the FOG myofiber has small elliptical axon terminals.…”
mentioning
confidence: 99%
“…The properties of muscle fibers are also associated with the different types of muscle in terms of size and innervation (e.g., cat, Nystrom, 1968; rabbit, Dias and Spimpson, 1974; rat, Lomo and Wwhaug, 1985). The size of endplates suggests a relationship to the size of muscle fibers (mouse, Ogata, 1965;Harris and Ribchester, 1979;Padykular and Gauthier, 1970). Large endings make large contributions to movements (Rosenheimer, 1985).…”
Section: Light Microscopic and Scanning Electron Microscopic Observatmentioning
confidence: 99%
“…However, there is conflicting evidence whether the morphology of the endplate is related to fibre type (Burke, 1981). Other studies have found that slow fibres have smaller endplates (Ogata, 1965;Harris and Ribchester, 1979;Padykula and Gauthier, 1970). Slow-twitch muscles are the most frequently activated, therefore a large endplate may be of advantage if it contained a larger supply of transmitter.…”
Section: The Endplatementioning
confidence: 99%